EISCAT and ESRAD radars observations of polar mesosphere winter echoes during solar proton events on 11–12 November 2004 - E. Belova; S. Kirkwood; T. Sergienko (Annales Geophysicae, 2013)
Polar mesosphere winter echoes (PMWE) were detected by two radars, ESRAD at 52 MHz located near Kiruna, Sweden, and EISCAT at 224 MHz located near Tromsø, Norway, during the strong solar proton event on 11–12 November 2004. PMWE maximum volume reflectivity was estimated to be 3 × 10 −15 m −1 for ESRAD and 2 × 10 −18 m −1 for EISCAT. It was found that the shape of the echo power spectrum is close to Gaussian inside the PMWE layers, and outside of them it is close to Lorentzian, as for the standard ion line of incoherent scatter (IS). The EISCAT PMWE spectral width is about 5–7 m s −1 at 64–67 km and 7–10 m s −1 at 68–70 km. At the lower altitudes the PMWE spectral widths are close to those for the IS ion line derived from the EISCAT data outside the layers. At the higher altitudes the PMWE spectra are broader by 2–4 m s −1 than those for the ion line. The ESRAD PMWE spectral widths at 67–72 km altitude are 3–5 m s −1 , that is, 2–4 m s −1 larger than ion line spectral widths modelled for the ESRAD radar. The PMWE spectral widths for both EISCAT and ESRAD showed no dependence on the echo strength. It was found that all these facts cannot be explained by turbulent origin of the echoes. We suggested that evanescent perturbations in the electron gas generated by the incident infrasound waves may explain the observed PMWE spectral widths. However, a complete theory of radar scatter from this kind of disturbance needs to be developed before a full conclusion can be made.